Influence of social media fitness influencers’ credibility on users’ physical activity intentions - Lidong Wang; Xiuhong Li; Donghai Wang; Jianyong Zhu (Digital Health)
Objective This study explores how trustworthiness, expertise, and attractiveness of fitness influencers affect Chinese users’ attitudes, subjective norms, perceived behavioral control, and intentions to engage in fitness activities on social media. By integrating the Theory of Planned Behavior with source credibility theory, this research examines the effectiveness of digital health communication in China, offering a novel approach. Methods Data were collected through a cross-sectional survey using convenience sampling, targeting 339 active fitness video viewers on DouYin, China's premier short video platform. The survey was administered via the professional online platform Sojump.com. Participants, active followers of various fitness influencers, engaged with diverse types and durations of fitness videos. Confirmatory factor analysis and structural equation modeling validated the measurement and structural models, rigorously examining the hypothesized relationships within the study. Results Trustworthiness and expertise of influencers significantly influenced users’ attitudes and perceived behavioral control, crucially affecting their intentions to engage in fitness activities. Unlike trustworthiness and expertise, attractiveness had no significant impact on subjective norms. Gender did not moderate these effects, indicating a consistent influencer impact across male and female users. Conclusions This research underscores the critical role of credible fitness influencers in enhancing engagement with health-promotive behaviors on social media. It emphasizes that authenticity and reliability are more influential than attractiveness in promoting health behaviors. This study advances our understanding of effective health communication on social media and offers practical insights for leveraging influencer credibility in public health campaigns.